A concentrate on difficulties and potentially open doors looked at by feminist business visionaries in the tourism industry in India - Khushboo Bilal; Sajad Ahmad Bhat; Danish Iqbal Raina; Ajaz Dar (Journal of Rural Tourism, 2025)
Purpose - This article examines the challenges and opportunities faced by feminist women entrepreneurs in India's tourism industry, focusing on the originality of their business approaches. It aims to explore how these women navigate gender-related barriers while also identifying opportunities for innovation and empowerment within the industry.Methodology/Design/Approach - The article analyzes the experiences of feminist women entrepreneurs in the tourism sector, looking at the structural barriers they face—such as discrimination and unequal access to resources—and the opportunities they find for innovation. The study emphasizes sustainable business practices, community-based empowerment, and gender-inclusive tourism. Finding - The findings reveal that while women entrepreneurs in tourism face significant gender-related challenges, they also create innovative and empowering business models. These models not only overcome barriers like discrimination and stereotypes but also contribute to the development of a more inclusive and sustainable tourism industry. The entrepreneurs highlight opportunities for promoting sustainable practices and gender-inclusive tourism. Originality/Value - The study offers fresh insights into the role of feminist women entrepreneurs in driving social and economic change within India’s tourism sector. It underscores their contributions to shaping a more inclusive and sustainable industry by creating original business models that challenge traditional gender norms and promote empowerment.